Q. 244.8( 4 Votes )

# In any triangle ABC, prove the following:

Answer :

Let a, b, c be the sides of any triangle ABC. Then by applying the sine rule, we get

⇒ a = k sin A, b = k sin B, c = k sin C

So by considering the LHS of the given equation, we get

Substituting the corresponding values from sine rule, we get

Rearranging we get

Regrouping this we get

But

Hence the above equation becomes,

(by applying sine rule)

Hence proved

Rate this question :

In any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

a cos A + b cos B + c cos C = 2b sin A sin C = 2c sin A sin B

RD Sharma - MathematicsIn any triangle ABC, prove the following:

a(sin B – sin C) + b(sin C – sin A) + c(sin A – sin B) = 0

RD Sharma - MathematicsIn any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

a^{2} sin (B – C) = (b^{2} – c^{2}) sin A

In any triangle ABC, prove the following:

RD Sharma - Mathematics

In any triangle ABC, prove the following:

b cos B + c cos C = a cos (B – C)

RD Sharma - MathematicsIn any triangle ABC, prove the following:

a^{2} (cos^{2} B – cos^{2} C) + b^{2} (cos^{2} C – cos^{2} A) + c^{2} (cos^{2} A – cos^{2} B) = 0

In a ∆ABC, if sin^{2} A + sin^{2} B = sin^{2} C, show that the triangle is right angled.